Workshop on Designing Program Evaluations for Principals of SMK Kaur Regency - Sumarsih Sumarsih; Zakaria Zakaria (Asosiasi Profesi Multimedia Indonesia, 2022)
The purpose of this PPM is to 1) increase the knowledge of the head of SMK about the concept of school program evaluation design, 2) improve the ability of the principal in preparing the evaluation design of the school program. The training method (workshop) is carried out in three stages. The first stage provides material on program evaluation concepts, program evaluation models, and program evaluation designs. the second stage is the practice of preparing program evaluation instruments, the third stage is the practice of designing program evaluation designs. The data was collected using performance tests and the data were analyzed using the percentage technique. The results of community service principals have the knowledge and skills to develop program evaluation designs properly. This means that there is an increase in the ability of school principals in preparing program evaluation designs